Lifts and service lifts Part 10. Specification for the testing and inspection of electric and hydraulic lifts (BSI, 1986)
Lifts, Service lifts, Passenger lifts, Goods lifts, Hydraulically-operated devices, Electrically-operated devices, Lifting equipment, Materials handling equipment, Inspection, Maintenance, Performance testing, High-voltage tests, Earthing, Electrical insulation, Electrical resistance, Testing conditions, Technical documents, Safety devices, Buffers (mechanical)